Phylogenetic Study of Lempuk Fish (Gobiopterus sp.) in Ranu Grati Based on Mitochondrial DNA Sequence of Cytochrome Oxidase I (COI) Barcoding Region - Abd Rahem Faqih; Wahyu Endra Kusuma; Septi Anitasari; Dian Kartika Sari (Department of Aquaculture, 2021)
Lempuk fish (Gobiopterus sp.) is one of the local species in Ranu Grati. The high level of Lempuk fishing and the low level of awareness of Grati community on the importance of conservation and domestication efforts, as well as the taxonomy of the fish itself have threatened the population. Therefore, long-term efforts should be undertaken to preserve and identify the origin of Lempuk fish by conducting a molecular phylogenetic study based on COI. This study aimed to determine, analyze and describe the kinship and phylogenetic relationships of Lempuk fish (Gobiopterus sp.). This study used a descriptive method, starting from the specimen collection, extraction by the Phenol-Chloroform method and amplification by the PCR method, to the screening process. The data analysis method used the MEGA 5 application. Phylogenetic study used the Maximum Likelihood method with a bootstrap value of 1.000 times. The results showed that the intra-population genetic distance of Lempuk fish is low at 0.00%. Genetic distance between the population of Lempuk fish is relatively high with G. brachypterus from Malaysia of 22.4%, Central Java of 21.5%, and India of 21.4% and with G. lacustris from Malaysia of 22.5%, the Philippines of 21.6% %, Thailand of 19.7%, and with G. chuno and G. semivestitus of 21.2% and 23.6% accordingly. The phylogenetic study obtained showed the formation of a separate group that is different between Lempuk fish group and other Gobiopterus fish, supported by a bootsrap value of 99%.